علاقة المهارات القيادية لمديري عموم التربية والتعليم في العحافظات التعليمية بكفاءة مديري المدارس ورضاهم الوظيفي والتعليم في سلطنة عمان - Hamed Salim Said Al Noumani (Universiti Sains Islam Malaysia, 2024)
This study aimed to investigate the interrelationships among leadership skills of general education heads with the efficiency of school principals and their satisfaction in the sultanate of Oman. The study also examined the relationship between school principals' leadership skills and personality variables. The researcher used the regrassion and correlation descriptive methods with sample size = 598 school principals and their assistants. The researcher designed the scales used to conduct this study based on previous studies. The result of the alpha coefficient showed that the scales were valid for use due to ther high quality. Alpha coefficient values for items ranged from 79 to 96. The researcher used several statistical methods to achieve various research objectives, including the factor analysis and multiple linear regression analysis to study the relationships between these factors. The results of the multiple regression analysis showed that there is a statistically significant relationship between the leadership skills and the efficiency of the general managers of education and that has a strong direct relationship with the satisfaction of the school principals. The result of the analysis also showed that there is a relationship between leadership skills and personal variables in favour of males. The study recommended the need to strengthen the leadership skills of managers because of their positive relationship with their competence and satisfaction development.